CONCRETE PROPERTIES IMPROVEMENT OF SLAB TRACKS USING CHEMICAL ADDITIVES - Pristinskaya, V. V. (Science and Transport Progress, 2015)
Purpose. On the Railways of Ukraine a very large number of slab tracks are operated with cracks. Many scientific works of previous years are dedicated to improving the design of slab tracks. The main causes of defects are: poor exploitation of the track; insufficient physic-mechanical characteristics of concrete; poor quality of initial materials. It is therefore necessary to develop an optimum concrete mix for the manufacture of these concrete products. Methodology. To assess the impact of individual factors and effects of their interactions on properties of concrete mix and concrete method of experimental and statistical modeling was used. At this, methodological fundamentals of mathematical experiment planning in concrete technology and modern methods of optimization of composite materials were taking into account. Based on the obtained data during the planned experiment conducting, including15 studies and using the computer program MathCad, were obtained the regression equations, which describe the relevant physical and mechanical properties of concrete. On the basis of the equations with the help of computer program MATLAB R2012b the graphs were drawn, illustrating the dependences of system response from the changes of two factors at a fixed value of the third factor. Findings. Firstly was the analysis of cracks that occur in the process of operation in the constructions of slab tracks. Further reasons of possible occurrence of these cracks were presented. In the process of the conducted research the author has concluded that for rational concrete mix development it is necessary to conduct the planned experiment with the use of quality materials. It was established that to increase the strength, chemical additives should be added in to concrete mix, it will let reduce cement amount. Originality. Experiments proved the usage of modern chemical additives in order to improve the properties of concrete. Models were developed, reflecting characteristics of concrete strength. With their help one can optimize concrete composition. Practical value. Research proved that the usage of more sustainable concrete mix for production of slab tracks will increase their strength, and with it the reliability of these designs mechanical properties.